2023
DOI: 10.1007/s00442-023-05406-w
|View full text |Cite
|
Sign up to set email alerts
|

Limited impact of chytridiomycosis on juvenile frogs in a recovered species

Abstract: The amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd) has caused catastrophic frog declines on several continents, but disease outcome is mediated by a number of factors. Host life stage is an important consideration and many studies have highlighted the vulnerability of recently metamorphosed or juvenile frogs compared to adults. The majority of these studies have taken place in a laboratory setting, and there is a general paucity of longitudinal field studies investigating the influence of life st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Gut fungal are closely associated with host immunity and dietary digestion [ 72 74 ]. In this study, we found that although the abundance of animal pathogens was highest in the early winter period compared to the other three periods, there were no significant differences between the wintering periods.…”
Section: Discussionmentioning
confidence: 99%
“…Gut fungal are closely associated with host immunity and dietary digestion [ 72 74 ]. In this study, we found that although the abundance of animal pathogens was highest in the early winter period compared to the other three periods, there were no significant differences between the wintering periods.…”
Section: Discussionmentioning
confidence: 99%